Perceptions Of Indonesian Young Farmers Toward The Ministry Of Agriculture's Milenial Farmers Program And Business Activities (Case Study On Indonesian Millennial Farmer Ambassadors) - Hasta Ningsih, Dina; Rondhon, M. Mustopa; Putra Utama, Satria (Journal of Agri Socio Economics and Business, 2023)
The millennial farmer program is an activity for future agricultural regeneration by the Indonesian Ministry of Agriculture. Apart from potential natural resources, business opportunities in the agricultural sector will certainly be an attractive one for young farmers who also receive guidance and training in the millennial farmer program. The perceptions of young farmers will provide a new perspective on the agricultural sector which is considered old-fashioned, dirty and has lower income than other sectors. The research respondents were millennial farmer ambassadors from the Ministry of Agriculture representing each region in Indonesia. Data was collected using an online form and processed using a Likert scale. Presented with qualitative descriptive. The results showed that the factors that most influenced the perception of millennial farmers were the level of education and parental influence. The perception of millennial farmer ambassadors (X) regarding the millennial farmer program (Y) and business studies (Z) is very good. Path analysis with Partial Least Square (PLS) to see the relationship between exogenous and endogenous and intervening variables. Knowledge of the direct relationship between variable X to Y, variable X to Z, variable Y to Z, all three have a significantly positive effect. And the indirect relationship between variables X and Z through Y also has a significant positive effect.